Hydrodynamic evaluation of the effects of fluid physical properties and sieve tray geometry on entrainment and weeping - Moses, Royston Kyle (Stellenbosch : Stellenbosch University, 2015)
Thesis (MEng) -- Stellenbosch University, 2014.